Evaluation of Staged Payment Plan Program to Improve Collectability of Independent Participant Contributions - Ningtiyas, Sri Ayu; Puspandari, Dyah Ayu (Jurnal Jaminan Kesehatan Nasional, 2025)
The main problem causing high arrears among Independent Participant and Non-Employee participants is the lack of a strong mechanism to ensure continuous payment of contributions. This study aimed to explore the Staged Payment Plan Program (REHAB) as an effort to increase the collectability of contributions from independent participants at BPJS Kesehatan Yogyakarta Branch Office in 2023. This research uses with program evaluation method. there were 251,494 (11,65%) Independent Participant and Non-Employee participants, with 109,280 (62,33%) in arrears as of February 2023. However, only 6.53% of them registered for the REHAB program. The input component shows that many participants still do not know about this program. The REHAB process shows that digitalization in the implementation of the REHAB program has not been maximized; there is no data update and notification for the billing process to participants. Internal monitoring is carried out regularly however, there is no monitoring of participants. The results component shows that Independent Participants contributions is 80.89%, but this collectability includes all forms of revenues owned by BPJS Kesehatan. The conclusion is the REHAB program has not yet achieved its goal of helping independent participants pay off contribution arrears. Socialization carried out is still not optimal because it has not reached all levels of society. There has been no regular update of participant data or direct evaluation of participants. The implementation of the REHAB program has not been proven to contribute to collectability because there is no data on collectability achievements sourced from the REHAB program